A method for preparing nanosheets and application in proton exchange membranes
Ultrathin nanosheets are prepared through the diazo coupling reaction of aromatic amine diazonium salts and aromatic polyphenols, and blended with polybenzimidazole, which solves the problem of difficulty in mass preparation and doping of nanosheet materials and achieves high performance and high temperature. The preparation of proton exchange membrane improves the conductivity and phosphoric acid retention rate.
Patent Information
- Application Number
- CN202310011179.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-05
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-01-05
AI Technical Summary
It is difficult to prepare nanosheet materials in large quantities in the prior art, and these nanosheets are difficult to dopant in high-performance high-temperature proton exchange membrane materials, resulting in reduced conductivity and loss of phosphoric acid.
Through the diazo coupling reaction of aromatic amine diazonium salts and aromatic polyphenols in an alkaline environment, ultrathin nanosheets with high reactivity are prepared and blended with polybenzimidazole to form a high-temperature proton exchange membrane. .
The preparation of a highly compatible and high-performance mixed matrix membrane was achieved, which improved the phosphoric acid doping rate and conductivity, while inhibiting the loss of phosphoric acid and improving the stability of high-temperature fuel cells.
Smart Images

Figure CN116120545B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of two-dimensional nano material preparation technology and fuel cell diaphragm technology, and in particular to a nano sheet preparation method and application in a proton exchange membrane. Background Art
[0002] A fuel cell is an energy conversion device with high specific power, high specific energy, clean and environmentally friendly, and a wide range of fuels. Due to its many advantages and the urgent need to popularize clean energy, fuel cells are widely used in many fields such as power generation and cogeneration. Among them, proton exchange membrane fuel cells are considered to be the fuel cells with the greatest commercial value and wide application potential. The proton exchange membrane is the core component of the proton exchange membrane fuel cell, and its performance directly determines the overall performance of the fuel cell. Nowadays, the most mature proton exchange membrane is the perfluorosulfonic acid Nafion membrane developed by DuPont in the United States. It has high electrical conductivity and excellent chemical stability, but due to its high synthesis cost, high dependence on environmental humidity when transferring protons, and high fuel permeability, the large-scale commercial application of Nafion membrane is limited.
[0003] At present, high-temperature fuel cells provide a way to develop high-performance proton exchange membrane fuel cells, that is, the operating temperature of the fuel cell is higher than 120°C. High-temperature fuel cells can simplify the water and heat management system, while alleviating the poisoning of the catalyst by carbon monoxide produced by insufficient reaction. High-temperature proton exchange membranes usually adopt a proton transfer mode different from that of Nafion membranes, that is, proton transfer is carried out by loading non-volatile acids such as phosphoric acid as proton carriers. At present, phosphoric acid-doped polybenzimidazole membranes are considered to be the most promising high-temperature proton exchange membranes. Polybenzimidazole is a high-performance polymer with nitrogen heterocycles, which has excellent thermal and chemical stability, and can use the imidazole ring in its skeleton structure to adsorb phosphoric acid molecules, thereby obtaining proton transfer ability. It is generally believed that the proton transfer mechanism in phosphoric acid-doped polybenzimidazole membranes is a jumping mechanism, that is, protons continuously jump between phosphoric acid molecules and the imidazole ring structure in polybenzimidazole to achieve stable proton transfer. Chinese patent CN113698644A uses the nucleophilic substitution reaction of imidazole-chlorocyclotriphosphazene to prepare a polybenzimidazole membrane material with a cross-linked structure, so that the prepared membrane material has a higher phosphoric acid doping rate and better battery performance. However, since water is generated in the fuel cell reaction, during the cold start process, water molecules will be enriched on the surface of the high-temperature proton exchange membrane, which will cause the loss of phosphoric acid molecules loaded by the polybenzimidazole, resulting in a decrease in conductivity and battery performance. In addition, co-doping polybenzimidazole materials with metal organic framework materials can also achieve high-temperature proton exchange membrane materials with high conductivity and low phosphoric acid loss rate (reference: J.PowerSources, 2021, 507, 230316). This type of porous material with high specific surface area can be used to prepare high-temperature proton exchange membrane materials with high phosphoric acid doping rate, high conductivity, and low phosphoric acid loss rate, providing new ideas for the preparation of a new generation of high-stability and high-performance high-temperature proton exchange membranes.
[0004] The porous materials developed today can already achieve the properties of high specific surface area and high porosity structure, but since the synthesis and preparation process often requires complex monomer synthesis and high temperature and high pressure conditions, it is difficult to achieve large-scale preparation. In addition, nanofillers usually have compatibility issues with the doped matrix, resulting in uneven properties of the blended materials. Therefore, it is urgent to develop a nanosheet material that can be prepared in large quantities and has a simple synthesis method, and apply it to high-temperature proton exchange membrane materials to achieve the preparation of highly compatible and high-performance mixed matrix membranes. Summary of the invention
[0005] In order to solve the problem that it is difficult to prepare nanosheet materials in large quantities using existing methods, and the prepared nanosheets are difficult to be doped for use in high-performance and high-temperature proton exchange membrane materials, the present invention provides a method for preparing nanosheets and their application in proton exchange membranes.
[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0007] The present invention first provides a method for preparing a nanosheet, and the specific steps are as follows:
[0008] Step (1): adding an aromatic amine monomer to water, adding an inorganic acid thereto, mechanically stirring to completely dissolve the monomer, and placing the monomer in an environment of 0 to 10° C. to obtain an aromatic amine solution A;
[0009] Step (2): adding the prepared sodium nitrite aqueous solution dropwise to the aromatic amine solution A described in step (1), maintaining the temperature of the aromatic amine solution A at 0 to 10° C., stirring for 10 to 30 minutes, and obtaining a diazonium salt solution B;
[0010] Step (3): adding an inorganic base solution to the diazonium salt solution B in step (2), adjusting the pH of the diazonium salt solution B to 1 to 14, and obtaining a diazonium salt solution C;
[0011] Step (4): preparing an aromatic polyphenol organic solution to obtain an organic solution D;
[0012] Step (5): adding the organic solution D in step (4) dropwise into the diazonium salt solution C in step (3), stirring vigorously for 0.05 to 240 hours at a stirring speed of 100 to 8000 rpm, and maintaining the mixed solution at 0 to 10° C., and obtaining ultrathin nanosheets after post-treatment.
[0013] Preferably, in the step (1), the mass percentage concentration of the aromatic amine monomer is 0.01 to 50 wt %, and the volume fraction of the inorganic acid is 0.01 to 20 v / v %.
[0014] Preferably, the aromatic amine monomer in step (1) is p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, mesitylenetriamine, 1,2,4,5-phenylenetetramine, biphenylenediamine, 1,3,5-tris(4-aminophenyl)benzene, 4,4'-diaminodiphenylmethane or 4,4'-diaminobibenzyl;
[0015] The inorganic acid is concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid, or tetrafluoroboric acid.
[0016] Preferably, in the step (2), the ratio of the amount of sodium nitrite to the amount of amino groups in the aromatic amine is (1-5):1.
[0017] Preferably, in step (3), the inorganic alkaline solution is lithium hydroxide, sodium hydroxide, potassium hydroxide, cesium hydroxide), barium hydroxide, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, zinc hydroxide, copper hydroxide, iron hydroxide, lead hydroxide, cobalt hydroxide, chromium hydroxide, zirconium hydroxide, nickel hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or cesium carbonate.
[0018] Preferably, in step (4), the aromatic polyphenol is preferably hydroquinone, resorcinol, catechol, pyrogallol, 1,2,4,5-tetrahydroxybenzene, or biphenol.
[0019] Preferably, in the step (5), the thickness of the nanosheet is 2 to 5 nm.
[0020] The present invention also provides application of the nanosheet in preparing a high-temperature proton exchange membrane.
[0021] Preferably, the method for preparing the high temperature proton exchange membrane comprises:
[0022] Step 1: dispersing the above nanosheets in an organic solvent to obtain a nanosheet organic solvent dispersion;
[0023] Step 2: Mixing the nanosheet organic solvent dispersion prepared in step 1 with the polybenzimidazole solution to obtain a casting solution;
[0024] Step 3: Cast the casting solution of step 2 into a membrane to obtain a high-temperature proton exchange membrane.
[0025] Preferably, in the step 2, the mass ratio of the nanosheets to the polybenzimidazole in the nanosheet organic solvent dispersion is (0.005-0.4):1.
[0026] The principle of the present invention is that the aromatic amine diazonium salt used in the present invention can react with aromatic polyphenols in an alkaline environment to undergo a diazo coupling reaction, and the reaction site is the adjacent position of the phenolic hydroxyl group of the aromatic polyphenols; due to the high reactivity of the diazonium salt, the diazonium salt and the aromatic polyphenols can be placed in water-oil phases, thereby utilizing the confinement effect of the water-oil interface to inhibit their growth in the longitudinal direction, thereby preparing an ultra-thin nanosheet structure with two-dimensional properties; Figure 5 The ultra-thin nanosheets are internal proton transfer sites. One method is to transfer protons through the active hydrogen they possess, and the other is to achieve proton transfer through the adsorption of phosphoric acid. The prepared nanosheets can regulate the monomers involved in the diazo coupling reaction, thereby regulating the pore structure, specific surface area and other pore structure properties of the nanosheets. Since the nanosheets have smaller pores and rich specific surface area, more phosphoric acid molecules can be adsorbed after being doped with polybenzimidazole, and the loss of phosphoric acid in a humid environment can be suppressed through the confinement effect of the narrow pores, which is beneficial to the stability of high-temperature fuel cells.
[0027] Beneficial effects of the present invention
[0028] The present invention provides a method for preparing a nanosheet and an application thereof in a proton exchange membrane. The nanosheet utilizes the characteristics of high reactivity of a diazo coupling reaction of an aromatic amine type diazonium salt-aromatic polyphenol, and obtains a rich microphase oil-water interface by a rapid stirring method, thereby expanding the interface area, thereby realizing the preparation of a large number of nanosheet materials. This method can obtain organic porous polymer ultra-thin nanosheet materials with different specific surface areas and different pore structure characteristics by regulating the structures of aromatic amine monomers and aromatic polyphenol monomers. The thickness of the obtained ultra-thin nanosheet material is only 2-5 nm, and the nanosheet has a micron-level size.
[0029] The present invention also provides the use of the above-mentioned nanosheets in the preparation of high-temperature proton exchange membranes. The obtained nanosheets are doped and blended with polybenzimidazole to obtain a blended high-temperature proton exchange membrane material. Due to the rich pore structure of the nanosheets, the blended high-temperature proton exchange membrane can have a higher phosphate doping rate and higher conductivity. In addition, due to the confinement effect of the narrow pores, the phosphate loss rate of the blended high-temperature proton exchange membrane under high temperature and high humidity conditions can be greatly reduced. The conductivity of the blended high-temperature proton exchange membrane of the present invention at 160°C is 95.0mScm -1 The phosphoric acid loss rate of the blended high-temperature proton exchange membrane is only 26.3% under the conditions of 80°C and 40% relative humidity, while the phosphoric acid loss rate of the polybenzimidazole without ultra-thin nanosheets is 45.9% under the same conditions, indicating that the ultra-thin nanosheets of the present invention can effectively improve the conductivity and inhibit the loss of phosphoric acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the porous skeleton structure of the ultrathin nanosheet of Example 3;
[0031] Figure 2 This is an atomic force microscope image of the ultrathin nanosheet prepared in Example 3 of the method of the present invention;
[0032] Figure 3 This is the nitrogen adsorption-desorption curve of the ultrathin nanosheet of Example 3 at 77K;
[0033] Figure 4 This is a physical picture of the blended high-temperature proton exchange membrane doped with ultra-thin nanosheets in Example 1;
[0034] Figure 5 Schematic diagram of the transport sites for proton transfer inside the ultra-thin nanosheet;
[0035] Figure 6The temperature-conductivity change curve of the blended high-temperature proton exchange membrane and the undoped polybenzimidazole membrane in Example 3;
[0036] Figure 7 This is a curve showing the variation of the residual mass percentage-time of the blended high temperature proton exchange membrane and the undoped polybenzimidazole membrane of Example 2 in an environment of 80° C. and 40% relative humidity. DETAILED DESCRIPTION
[0037] The present invention first provides a method for preparing a nanosheet, and the specific steps are as follows:
[0038] Step (1): adding an aromatic amine monomer to water, and then adding an inorganic acid thereto, mechanically stirring to completely dissolve it, the stirring time is preferably 10 to 30 minutes, more preferably 10 to 25 minutes, and placing it in an environment of 0 to 10° C., preferably 0.5 to 7° C., to obtain an aromatic amine solution A; the mass percentage concentration of the aromatic amine monomer is preferably 0.01 to 50wt%, more preferably 5 to 36wt%, the volume fraction of the inorganic acid is preferably 0.01 to 20v / v%, more preferably 2 to 15v / v%, the aromatic amine monomer is preferably p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, mesitylenetriamine, 1,2,4,5-phenylenetetramine, biphenylenediamine, 1,3,5-tris(4-aminophenyl)benzene, 4,4'-diaminodiphenylmethane or 4,4'-diaminobibenzyl; the inorganic acid is concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid, or tetrafluoroboric acid.
[0039] Step (2): preparing a sodium nitrite aqueous solution with a mass concentration of preferably 0.1-10 w / v%, preferably a mass concentration of 0.2-5 w / v%, wherein the ratio of the amount of sodium nitrite to the amount of amino group in the aromatic amine is preferably (1-5):1, more preferably 1.8-3:1, and adding the prepared sodium nitrite aqueous solution dropwise to the aromatic amine solution A described in step (1), maintaining the temperature of the aromatic amine solution A at 0-10° C., preferably 5-7° C., stirring for 10-30 minutes, preferably 18-25 minutes, to obtain a diazonium salt solution B;
[0040] Step (3): adding an inorganic alkali solution to the diazonium salt solution B in step (2), adjusting the pH of the diazonium salt solution B to 1 to 14, preferably 5 to 9, to obtain a diazonium salt solution C; the mass concentration of the inorganic alkali solution is preferably 0.1 to 10 w / v%, more preferably 2 to 6 w / v%;
[0041] The inorganic base is preferably lithium hydroxide, sodium hydroxide, potassium hydroxide, cesium hydroxide), barium hydroxide, calcium hydroxide, aluminum hydroxide, magnesium hydroxide, zinc hydroxide, copper hydroxide, iron hydroxide, lead hydroxide, cobalt hydroxide, chromium hydroxide, zirconium hydroxide, nickel hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and cesium carbonate.
[0042] Step (4): preparing an aromatic polyphenol organic solution to obtain an organic solution D; the concentration of the aromatic polyphenol organic solution is preferably 0.001-5 mol / L, more preferably 0.008-2 mol / L; the aromatic polyphenol is preferably hydroquinone, resorcinol, catechol, pyrogallol, 1,2,4,5-tetrahydroxybenzene, biphenol;
[0043] The organic solvent used to prepare the organic solution is preferably benzene, toluene, chlorobenzene, xylene, mesitylene, dichloromethane, chloroform, tetrachloromethane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and butyl butyrate.
[0044] Step (5): adding the organic solution D in step (4) dropwise to the diazonium salt solution C in step (3), vigorously stirring for 0.05 to 240 hours, preferably 0.5 to 180 hours, at a stirring speed of 100 to 8000 rpm, preferably 200 to 3000 rpm, and maintaining the mixed solution at 0 to 10° C., preferably 2 to 8° C., to obtain a crude ultrathin nanosheet product, preferably separating the crude ultrathin nanosheet product from the mixed solution by filtration, and washing the crude ultrathin nanosheet product with an organic solution, and finally drying the washed nanosheet to obtain a nanosheet. The thickness of the nanosheet is preferably 2 to 5 nm.
[0045] In step (5), the organic solution used to wash the ultrathin nanosheets is benzene, toluene, chlorobenzene, xylene, mesitylene, dichloromethane, chloroform, tetrachloromethane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.
[0046] The present invention also provides application of the nanosheet in preparing a high-temperature proton exchange membrane.
[0047] Preferably, the method for preparing the high temperature proton exchange membrane comprises:
[0048] Step 1: Dispersing the above-mentioned nanosheets in an organic solvent to obtain a nanosheet organic solvent dispersion; the mass percentage of the nanosheets to the organic solvent is preferably 0.01-20wt%, more preferably 1-9wt%; the dispersion method is not particularly limited, preferably ultrasonic, the ultrasonic treatment time is preferably 1-480 minutes, more preferably 20-400 minutes, and the dispersion solvent is preferably N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone.
[0049] Step 2: Mix the nanosheet organic solvent dispersion and the polybenzimidazole solution of step 1, stir evenly, and obtain a casting solution; the mass percentage of the polybenzimidazole solution after mixing is 0.1-50wt%, more preferably 4-15wt%; the mass percentage of the polybenzimidazole solution is preferably 0.1-20wt%, more preferably 4-18wt%; the mass ratio of the nanosheets and the polybenzimidazole in the nanosheet organic solvent dispersion is preferably (0.005-0.4):1, more preferably 0.01-0.2:1.
[0050] Step 3: Cast the casting solution in step 2 into a membrane to obtain a high-temperature proton exchange membrane. The thickness of the high-temperature proton exchange membrane is preferably 1 to 1000 microns, more preferably 40 to 500 microns.
[0051] After performing step three, the blended high-temperature proton exchange membrane obtained in the present invention needs to be post-treated, and the post-treatment conditions and steps are as follows: first, the blended high-temperature proton exchange membrane obtained in the present invention is immersed in 85% phosphoric acid at 120°C for 24 hours, and then the blended high-temperature proton exchange membrane soaked in phosphoric acid is dried in a vacuum oven at a drying temperature of 120°C for more than 24 hours, and then stored in a nitrogen environment for standby use.
[0052] The ultra-thin nanosheets prepared by the diazo coupling reaction provided by the present invention have excellent two-dimensional properties, a thickness of only 2 to 5 nm, and the ability to be prepared in large quantities, so that they can be used as nanofillers and blended with polybenzimidazole to prepare a blended high-temperature proton exchange membrane. The ultra-thin nanosheets are prepared by the diazo coupling reaction at the microphase interface, and in addition, the preparation of nanosheet materials with different pore structures and different specific surface areas can be achieved by adjusting the monomer structure of aromatic amines and aromatic polyphenols.
[0053] The present invention is further described in detail below with reference to the examples. The raw materials involved in the examples are all commercially available.
[0054] Example 1
[0055] Add 4,4'-diaminodiphenylmethane with a mass percentage concentration of 5wt% to water, then add nitric acid with a volume fraction of 2v / v%, mechanically stir for 15 minutes to completely dissolve it, and place it in an environment of 3°C to obtain a 4,4'-diaminodiphenylmethane solution, which is stored at 3°C for standby use. Prepare a sodium nitrite aqueous solution with a mass concentration of 0.35w / v%, wherein the ratio of the amount of sodium nitrite to the amount of 4,4'-diaminodiphenylmethane amino group is 2.6:1, and add the prepared sodium nitrite aqueous solution dropwise to the above 4,4'-diaminodiphenylmethane solution, keep the temperature of the 4,4'-diaminodiphenylmethane solution at 5°C, stir for 18 minutes, add a sodium hydroxide solution with a mass concentration of 3w / v%, adjust the pH to 7, obtain a diazonium salt phase solution, and store it at 3°C for standby use. Prepare a 0.008mol / L pyrogallol / toluene solution to obtain an organic phase solution. The pyrogallol / toluene solution was added dropwise to the diazo salt phase solution, and the mixture was stirred vigorously for 96 hours at a stirring speed of 1600 rpm, and the mixed solution was kept at 8°C to obtain a crude ultrathin nanosheet product. The crude ultrathin nanosheet product was separated from the mixed solution by filtration, and the crude ultrathin nanosheet product was washed with methanol. Finally, the washed nanosheet was dried to obtain an ultrathin nanosheet.
[0056] The obtained ultra-thin nanosheets are dispersed in N-methylpyrrolidone by ultrasonic treatment, the mass percentage of the ultra-thin nanosheets and the organic solvent is 1wt%, and the ultrasonic treatment time is 400 minutes, so as to obtain the N-methylpyrrolidone dispersion of the ultra-thin nanosheets. A polybenzimidazole solution with a mass percentage of 5wt% is prepared with N-methylpyrrolidone and stirred until fully dissolved. The N-methylpyrrolidone dispersion of the ultra-thin nanosheets is mixed with the polybenzimidazole solution to prepare a solution with a mass percentage of 8wt% of the polybenzimidazole after mixing, and in the prepared solution, the mass ratio of the ultra-thin nanosheets to the polybenzimidazole is 0.2:1. The mixed solution of the ultra-thin nanosheets-polybenzimidazole is prepared into a homogeneous membrane with a thickness of 100 microns by a casting machine, and the obtained is a blended high-temperature proton exchange membrane.
[0057] The obtained blended high-temperature proton exchange membrane needs to be soaked in 85% phosphoric acid at 120°C for 24 hours, and then the blended high-temperature proton exchange membrane soaked in phosphoric acid is dried in a vacuum oven at a drying temperature of 120°C for 48 hours, and then stored in a nitrogen environment to obtain a phosphoric acid-doped blended high-temperature proton exchange membrane for standby use.
[0058] The prepared ultrathin nanosheets have a BET specific surface area of 136.9 m 2 g -1 , the pore size is mainly distributed at 6nm, and the thickness of the nanosheet is 7nm.
[0059] The test results show that the phosphoric acid doping amount of the phosphoric acid-doped blended high-temperature proton exchange membrane is 248.9%.
[0060] The conductivity change of the phosphoric acid-doped blended high-temperature proton exchange membrane at different temperatures and its phosphoric acid retention rate in an environment of 80°C and 40% relative humidity were tested. The phosphoric acid retention rate was obtained by testing the mass change of the phosphoric acid-doped blended high-temperature proton exchange membrane under humidity conditions.
[0061] The performances are shown in Table 1 and Table 2 respectively.
[0062] Table 1 Conductivity changes
[0063]
[0064] Table 2 Changes in phosphoric acid retention rate
[0065]
[0066] Figure 4 This is a physical picture of the blended high-temperature proton exchange membrane doped with ultra-thin nanosheets in Example 1. As shown in the figure, the polybenzimidazole blended membrane doped with nanosheets still has high transparency and no obvious unevenness is found, indicating that the interface compatibility between the nanosheets and polybenzimidazole is good and the properties of the membrane are uniform;
[0067] Example 2
[0068] Add 20wt% of phenyltriamine to water, add 10v / v% hydrochloric acid, stir mechanically for 25 minutes to completely dissolve it, and place it in a 7°C environment to obtain a phenyltriamine solution, which is stored at 4°C for standby use. Prepare a 4w / v% sodium nitrite aqueous solution, in which the ratio of the amount of sodium nitrite to the amount of amino group of phenyltriamine is 3:1, add the prepared sodium nitrite aqueous solution dropwise to the above phenyltriamine solution, keep the temperature of the phenyltriamine solution at 7°C, stir for 25 minutes, add 6w / v% cesium carbonate solution, adjust the pH to 8, obtain a diazonium salt phase solution, store at 5°C for standby use. Prepare a 2mol / L hydroquinone / methyl propionate solution to obtain an organic phase solution. The hydroquinone / methyl propionate solution was added dropwise to the diazonium salt phase solution, and the mixture was stirred vigorously for 180 hours at a stirring speed of 3000 rpm, and the mixed solution was kept at 2°C to obtain a crude ultrathin nanosheet product. The crude ultrathin nanosheet product was separated from the mixed solution by filtration, and the crude ultrathin nanosheet product was washed with N-methylpyrrolidone. Finally, the washed nanosheet was dried to obtain an ultrathin nanosheet.
[0069] The obtained ultrathin nanosheets are dispersed in N,N-dimethylacetamide by ultrasonic treatment, the mass percentage of the ultrathin nanosheets to the organic solvent is 9wt%, the ultrasonic treatment time is 20 minutes, and the N,N-dimethylacetamide dispersion of the ultrathin nanosheets is obtained. A polybenzimidazole solution with a mass percentage of 15wt% is prepared with N,N-dimethylacetamide and stirred until fully dissolved. The N,N-dimethylacetamide dispersion of the ultrathin nanosheets is mixed with the polybenzimidazole solution to prepare a solution with a mass percentage of 15wt% of the polybenzimidazole after mixing, and in the prepared solution, the mass ratio of the ultrathin nanosheets to the polybenzimidazole is 0.01:1. The mixed solution of the ultrathin nanosheets-polybenzimidazole is prepared into a homogeneous membrane with a thickness of 500 microns by a casting machine, and the obtained is a blended high-temperature proton exchange membrane.
[0070] The obtained blended high-temperature proton exchange membrane needs to be soaked in 85% phosphoric acid at 120°C for 24 hours, and then the blended high-temperature proton exchange membrane soaked in phosphoric acid is dried in a vacuum oven at a drying temperature of 120°C for 24 hours, and then stored in a nitrogen environment to obtain a phosphoric acid-doped blended high-temperature proton exchange membrane for standby use.
[0071] The prepared ultrathin nanosheets have a BET specific surface area of 469.5 m 2 g -1 , the pore size is mainly distributed at 3nm, and the thickness of the nanosheet is 4.5nm.
[0072] The test results show that the phosphoric acid doping amount of the phosphoric acid-doped blended high-temperature proton exchange membrane is 278.9%.
[0073] The conductivity change of the phosphoric acid-doped blended high-temperature proton exchange membrane at different temperatures and its phosphoric acid retention rate in an environment of 80°C and 40% relative humidity were tested. The phosphoric acid retention rate was obtained by testing the mass change of the phosphoric acid-doped blended high-temperature proton exchange membrane under humidity conditions.
[0074] The performances are shown in Table 3 and Table 4 respectively.
[0075] Table 3 Conductivity changes
[0076]
[0077]
[0078] Table 4 Changes in phosphoric acid retention rate
[0079]
[0080] Figure 7This is a curve of the variation of the residual mass percentage-time of the blended high-temperature proton exchange membrane and the undoped polybenzimidazole membrane in Example 2 in an environment of 80°C and 40% relative humidity. The figure shows that compared with the polybenzimidazole membrane, the blended high-temperature proton exchange membrane doped with ultra-thin nanosheets has a higher phosphate retention capacity due to the confinement effect of the narrow pores of the nanosheets.
[0081] Example 3
[0082] Add p-phenylenediamine with a mass percentage concentration of 36wt% to water, then add sulfuric acid with a volume fraction of 15v / v%, mechanically stir for 10 minutes to completely dissolve it, and place it in an environment of 0.5°C to obtain a phenyltriamine solution, which is stored at 2°C for standby use. Prepare a sodium nitrite aqueous solution with a mass concentration of 0.2w / v%, wherein the ratio of the amount of sodium nitrite to the amount of amino group of phenyltriamine is 2:1, and add the prepared sodium nitrite aqueous solution dropwise to the above phenyltriamine solution, keep the temperature of the phenyltriamine solution at 2°C, stir for 30 minutes, add a cobalt hydroxide solution with a mass concentration of 2w / v%, adjust the pH to 5, obtain a diazonium salt phase solution, and store it at 2°C for standby use. Prepare a biphenylphenol / chloroform solution with a concentration of 0.09mol / L to obtain an organic phase solution. The p-biquinone / chloroform solution was added dropwise to the diazonium salt phase solution, stirred vigorously for 0.5 hours at a stirring speed of 200 rpm, and the mixed solution was kept at 2°C to obtain a crude ultrathin nanosheet product. The crude ultrathin nanosheet product was separated from the mixed solution by filtration, and the crude ultrathin nanosheet product was washed with N,N-dimethylformamide. Finally, the washed nanosheet was dried to obtain an ultrathin nanosheet.
[0083] The obtained ultrathin nanosheets are dispersed in N,N-dimethylformamide by ultrasonic treatment, the mass percentage of the ultrathin nanosheets to the organic solvent is 20wt%, the ultrasonic treatment time is 360 minutes, and the N,N-dimethylformamide dispersion of the ultrathin nanosheets is obtained. A polybenzimidazole solution with a mass percentage of 18wt% is prepared with N,N-dimethylformamide and stirred until fully dissolved. The N,N-dimethylformamide dispersion of the ultrathin nanosheets is mixed with the polybenzimidazole solution to prepare a solution with a mass percentage of 4wt% of the polybenzimidazole after mixing, and in the prepared solution, the mass ratio of the ultrathin nanosheets to the polybenzimidazole is 0.04:1. The mixed solution of the ultrathin nanosheets-polybenzimidazole is prepared into a homogeneous membrane with a thickness of 40 microns by a casting machine, and the obtained is a blended high-temperature proton exchange membrane.
[0084] The obtained blended high-temperature proton exchange membrane needs to be soaked in 85% phosphoric acid at 120°C for 24 hours, and then the blended high-temperature proton exchange membrane soaked in phosphoric acid is dried in a vacuum oven at a drying temperature of 120°C for 24 hours, and then stored in a nitrogen environment to obtain a phosphoric acid-doped blended high-temperature proton exchange membrane for standby use.
[0085] The prepared ultrathin nanosheets have a BET specific surface area of 506.2 m 2 g -1 , the pore size is mainly distributed at 1.4nm, and the thickness of the nanosheet is 3nm.
[0086] The test results show that the phosphoric acid doping amount of the phosphoric acid-doped blended high-temperature proton exchange membrane is 298.3%.
[0087] The conductivity change of the phosphoric acid-doped blended high-temperature proton exchange membrane at different temperatures and its phosphoric acid retention rate in an environment of 80°C and 40% relative humidity were tested. The phosphoric acid retention rate was obtained by testing the mass change of the phosphoric acid-doped blended high-temperature proton exchange membrane under humidity conditions.
[0088] The performances are shown in Table 5 and Table 6 respectively.
[0089] Table 5 Conductivity changes
[0090]
[0091] Table 6 Changes in phosphoric acid retention rate
[0092]
[0093]
[0094] Figure 1 Schematic diagram of the porous skeleton structure of the ultrathin nanosheet of Example 3;
[0095] Figure 2 This is an atomic force microscope image of the ultrathin nanosheet prepared in Example 3 of the method of the present invention, which shows that the prepared ultrathin nanosheet has a good two-dimensional structure;
[0096] Figure 3 The nitrogen adsorption-desorption curve of the ultrathin nanosheet of Example 3 at 77K. The BET specific surface area calculated by DFT method is 506.2 m 2 g -1 .
[0097] Figure 6The temperature-conductivity change curve of the blended high-temperature proton exchange membrane and the undoped polybenzimidazole membrane in Example 3 shows that at the operating temperature of the high-temperature proton exchange membrane fuel cell (120-180° C.), the blended high-temperature proton exchange membrane doped with ultrathin nanosheets has a higher proton conductivity than the undoped polybenzimidazole;
[0098] Comparative Example 1
[0099] The polybenzimidazole membrane without doping ultra-thin nanosheets is prepared into a homogeneous membrane with a thickness of 40 microns by a casting machine. The obtained undoped polybenzimidazole high-temperature proton exchange membrane is immersed in 85% phosphoric acid at 120°C for 24 hours, and then the high-temperature proton exchange membrane immersed in phosphoric acid is dried in a vacuum oven at a drying temperature of 120°C for 24 hours, and then stored in a nitrogen environment to obtain an undoped high-temperature proton exchange membrane for standby use.
[0100] The test results show that the phosphoric acid doping amount of the phosphoric acid-doped blended high-temperature proton exchange membrane is 221.3%.
[0101] The conductivity change of the phosphoric acid-doped undoped polybenzimidazole high temperature proton exchange membrane at different temperatures and its phosphoric acid retention rate in an environment of 80°C and 40% relative humidity were tested. The phosphoric acid retention rate was obtained by testing the mass change of the phosphoric acid-doped high temperature proton exchange membrane under humidity conditions.
[0102] The performances are shown in Table 7 and Table 8 respectively.
[0103] Table 7 Conductivity changes
[0104]
[0105]
[0106] Table 8 Changes in Phosphoric Acid Retention Rate
[0107]
[0108] In summary, the blended high-temperature proton exchange membrane doped with ultra-thin nanosheets has obvious performance advantages, specifically: as shown in Table 9, the blended high-temperature proton exchange membrane has a high phosphoric acid doping rate and a low sulfuric acid loss rate. This is because the rich pore structure of the ultra-thin nanosheets can provide more phosphoric acid adsorption space and achieve a higher phosphoric acid doping rate. In addition, the phosphoric acid retention rate of the undoped polybenzimidazole high-temperature proton exchange membrane is much lower than that of the blended high-temperature proton exchange membrane doped with ultra-thin nanosheets. This is because the narrow pores of the ultra-thin nanosheets will confine the doped phosphoric acid, thereby inhibiting its loss under high temperature and high humidity conditions. Therefore, ultra-thin nanosheets are conducive to the preparation of high-temperature proton exchange membrane materials with high phosphoric acid doping amounts and high phosphoric acid retention rates.
[0109] Table 9 Phosphoric acid doping rate, conductivity at 160 °C and phosphoric acid retention rate for 50 hours of different membranes
[0110]
[0111]
[0112] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. An application of a nanosheet in preparing a high-temperature proton exchange membrane, characterized in that: The preparation method of the nanosheets comprises the following specific steps: Step (1): adding an aromatic amine monomer to water, adding an inorganic acid thereto, mechanically stirring to completely dissolve the aromatic amine monomer, and placing the aromatic amine monomer in an environment of 0 to 10° C. to obtain an aromatic amine solution A; the aromatic amine monomer is p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, mesitylenetriamine, 1,2,4,5-phenylenetetramine, biphenylenediamine, 1,3,5-tris(4-aminophenyl)benzene, 4,4'-diaminodiphenylmethane or 4,4'-diaminobibenzyl; Step (2): adding the prepared sodium nitrite aqueous solution dropwise to the aromatic amine solution A described in step (1), maintaining the temperature of the aromatic amine solution A at 0 to 10° C., stirring for 10 to 30 minutes, and obtaining a diazonium salt solution B; Step (3): adding an inorganic base solution to the diazonium salt solution B in step (2), adjusting the pH of the diazonium salt solution B to 1 to 14, and obtaining a diazonium salt solution C; Step (4): preparing an aromatic polyphenol organic solution to obtain an organic solution D; Step (5): adding the organic solution D in step (4) dropwise to the diazonium salt solution C in step (3), stirring vigorously for 0.05 to 240 hours at a stirring speed of 100 to 8000 rpm, obtaining a rich microphase oil-water interface by rapid stirring, and maintaining the mixed solution at 0 to 10° C., and obtaining nanosheets after post-treatment.
2. The use according to claim 1, characterized in that: In the step (1), the mass percentage concentration of the aromatic amine monomer is 0.01 to 50 wt%, and the volume fraction of the inorganic acid is 0.01 to 20 v / v%.
3. The use according to claim 1, characterized in that: The inorganic acid is concentrated hydrochloric acid, concentrated sulfuric acid, concentrated nitric acid, or tetrafluoroboric acid.
4. The use according to claim 1, characterized in that: In the step (2), the ratio of the amount of sodium nitrite to the amount of amino groups in the aromatic amine is (1-5):
1.
5. The use according to claim 1, characterized in that: In the step (3), the inorganic alkaline solution is lithium hydroxide, sodium hydroxide, potassium hydroxide, cesium hydroxide, barium hydroxide, calcium hydroxide, ammonium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate or cesium carbonate.
6. The use according to claim 1, characterized in that: In the step (4), the aromatic polyphenol is hydroquinone, resorcinol, catechol, pyrogallol, 1,2,4,5-tetrahydroxybenzene or biphenol.
7. The use according to claim 1, characterized in that: In the step (5), the thickness of the nanosheet is 2 to 5 nm.
8. The use according to claim 1, characterized in that: The method for preparing the high-temperature proton exchange membrane comprises: Step 1: dispersing the above nanosheets in an organic solvent to obtain a nanosheet organic solvent dispersion; Step 2: Mixing the nanosheet organic solvent dispersion prepared in step 1 with the polybenzimidazole solution to obtain a casting solution; Step 3: Cast the casting solution of step 2 into a membrane to obtain a high-temperature proton exchange membrane.
9. The use according to claim 8, characterized in that: In the step 2, the mass ratio of the nanosheets to the polybenzimidazole in the nanosheet organic solvent dispersion is (0.005-0.4):1.
Citation Information
Patent Citations
Crosslinked polybenzimidazole membrane material for high-temperature proton exchange membrane and preparation method of cross-linked polybenzimidazole membrane material
CN113698644A
Preparation method of silicon-carbon composite negative electrode material of lithium ion battery and application of silicon-carbon composite negative electrode material
CN104362300A
Dianhydride monomer with side chains containing phenylacetylene and synthesis method and application of dianhydride monomer
CN108586403A